The Effect of Work Stress, Work Family Conflict, Organizational Climate, and Organizational Support Burn Out on Employee at Company - Lujeng Iswahyuni; Rifdah Abadiyah (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine the effect of work stress, work family conflict, organizational climate and organizational support on burnout at PT. Welirang Tirta Mandiri. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity and reliability tests. The hypothesis in this study is that there is the effect of work stress, work family conflict, organizational climate and organizational support on burnout. To test this hypothesis used data analysis tools in the form of multiple linear regression. The results of the research show that work stress, work family conflict, organizational climate, and organizational support has a positive effect on burnout. And simultaneously work stress, work family conflict, organizational climate and organizational support have a positive effect on burnout.